Cricova - The National and International Tourist Brand of The Republic of Moldova - Vadim Cujbă; Rodica Sîrbu (Jan Długosz University in Częstochowa, 2020)
This article, presents the results of the research on the creation, organization, administration and promotion of the Cricova wine complex. In this, representative elements ensuring the attractiveness of the town from the tourist point of view have been identified. The Cricova wine complex is a system of underground galleries created after the extraction of conchiferous limestone since ancient times. The idea of​using these galleries as wine warehouses was agreed upon by winemakers Petru Ungureanu and Nicolae Sobolev, in response to solving the problem of the lack of specially designed rooms for storing, processing and maturing wines from the 1950s. Currently, the complex covers the area of 53 hectares, and the underground galleries transformed into streets have a total length of 120 kilometers. Throughout the year, the temperature in the underground galleries remains constant, around + 12...+ 14 °C and the relative air humidity is around 97-98%. The uniqueness of the Underground Complex provides material and spiritual heritage of the tasting rooms, a museum with exhibits from all times (prehistoric, ancient, medieval and modern), a national wine collection with over 200 wine brands from different regions of the world, organizing tourist events.